TLR4 macrophage expression of the wistar rats were inoculated by Candida albicans - I Dewa Ayu Ratna Dewanti (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Multidimentional crisis in Indonesia caused to multi effects. In heatlh aspect caused increase infection diseases, otherwhise mouth become some gate for entrance pathogen flora into human body. One of the most infection diseases was found in the mouth is candidiasis caused by C albicans. TLR4 were play a pivotal role in recognition of Candida albicans.The purposed experimental : This experimental purposed to know comparation of TLR4 expression macrophage of the wistar rats were inoculated C albicans. Method : The subjects of this research are 20 male-wistar rats divided into five groups : Control Group (KO) were 10 rats that were not given treatment. Experimental Groups (KP), 10 rats that were inoculated by C albicans. After 21 days, will been kill and cut on tongue for analized by imunohistochemic. The data obtained will be analyzed using t test. The result : The result this research showed that there was not a significant different (p<0,05) to comparation of TLR4 macrophage expression of Experimental Groups 1 (KP). A significant different was found at decreasing of TLR4 between KO with KP Discused : These decreasing are assumed that C albicans infection could inhibit TLR4 activities, so the decreasing of macrophage activity caused TLR4 decreased. All of those activity causes the decreasing immune response and killed activity to C albicans. The conclusion : The fact of this research is dereasing TLR4 macrophage of wistar rat was inoculated by C albicans.